Rural Educational Attainment: The Importance of Context - Sarah Schmitt-Wilson; Jayne A. Downey; Ashley E. Beck (Journal of Research in Rural Education, 2018)
Understanding patterns of educational attainment among rural youth is a critical concern for our nation as we seek to make postsecondary access and attainment more equitable across our increasingly diverse student population. The current study examines data collected in the Education Longitudinal Study of 2002 to identify contemporary patterns of educational attainment among rural youth, with a focus on associate degree attainment and bachelor's degree attainment. Findings reveal that education expected for occupation is a signifi cant predictor for bachelor's degree attainment, with regional diff erences found among individuals earning a bachelor's degree. The results support a link between rural students' expectations for occupation and educational attainment and highlight diff erences in educational attainment by region of residence.